Working from home? Follow these tips for successful remote work. Issue 2 (27th April 2020) - Hope, Joan
Abstract : So you're asked to work from home as COVID‐19 cases spread. Some jobs lend themselves to remote work better than others, but if your college or university says it's time to head home, you can accomplish a lot, no matter what your job responsibilities entail.